The Influence of Part-Time Job on The Financial Independence of Students (A Study on Students of The Faculty of Economics at Unitri) - Valentina Ancelina Nina; Nur Ida Iriani; Warter Agustim (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this research is to determine the effect of part-time jobs on the financial independence of students in the economics faculty of UNITRI. The research conducted is a quantitative study. The sample determination for this research uses purposive sampling, resulting in a sample size of 30 respondents. The data collection technique used by the researcher is a questionnaire. The data analysis method employed is simple linear regression using SPSS 26 software. The research results prove that part-time jobs have a significant effect on the financial independence of students in the economics faculty of UNITRI, as the calculated t value is 4.520, indicating an influence of 72.1%. Part-time jobs provide students with a source of income that can be used to meet daily needs, thereby improving the financial independence of students.